Conditions for exercising shareholders' right to ask questions - Radović Vuk (Anali Pravnog Fakulteta u Beogradu)
Law on Business Organizations from 2011 has significantly improved the regulation of shareholders' right to ask questions in Serbia. In contrast to the previous law from 2004, that has completely transferred regulation to companies which is why there was no guarantee for exercising this right, new law contains detailed norms in this respect. They are written under the dominant influence of German law and are completely harmonized with the Shareholders' Rights Directive. All important issues of shareholders' right to ask questions have been regulated mostly with imperative norms (subject of the right, conditions for exercising this right, debtor of this obligation, court protection, etc.). Corporations have a lot of freedom to adjust exercising this right to their needs, but only by giving more rights to shareholders. Limiting the scope of this right is possible only in certain, precisely defined areas. Although the general impression of the new regulation is very positive, there are certain aspects which can be criticized. Some of them can be cured by adequate judicial interpretation, while others cannot be cured without changes to the law. In the area of conditions for exercising this right, the most important deficiency is the fact that the law has not determined when the right to ask questions can be exercised, and that stands in obvious disharmony with the adopted conception to regulate all important aspects of this right. Contrary to conditions, which basically have been properly formulated, other aspects of legislation regarding this shareholders' right contain more profound obscurities that go beyond the scope of this paper.